(untitled) (Journal of Mathematical Study, 2015)
Some sharp estimates for coefficients, distortion and the growth order are obtained for harmonic mappings f ∈ TL^α_H which are locally univalent harmonic mappings in the unit disk D:={z:|z| < 1}. Moreover, denoting the subclass TS^α_H of the normalized univalent harmonic mappings, we also estimate the growth of |f|, f ∈ TS^α_H, and their covering theorems.